2009
DOI: 10.1089/jmf.2008.0176
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Garlic in Young and Aged Rat Brain In Vitro

Abstract: Oxidative stress plays a key role in the pathogenesis of age-related neurodegeneration, and the nonenzymatic production of 8-iso-prostaglandin F(2alpha) (8-iso-PGF(2alpha)) may represent a reliable index of cellular oxidative damage. Garlic (Allium sativum) has been associated with peripheral antioxidant activities and therefore might prevent or reverse 8-iso-PGF(2alpha) production, but scant data are available on its possible neuroprotective effects. Therefore, we have studied the possible antioxidant effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The importance of the assessment of inhibition ability of lipid peroxidation is due to the negative influence towards neurodegenerative disorders [20,21], above all during aging [22]. For this reason, herbal drug supplementation that contains antioxidant compounds could improve the oxidative stress induced by aging and neurodegenerative conditions [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…The importance of the assessment of inhibition ability of lipid peroxidation is due to the negative influence towards neurodegenerative disorders [20,21], above all during aging [22]. For this reason, herbal drug supplementation that contains antioxidant compounds could improve the oxidative stress induced by aging and neurodegenerative conditions [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…These oil-soluble components exhibit antioxidant properties, by reducing the levels of reactive oxygen species and increasing glutathione- S -transferase expression [19, 20]. In previous studies, we demonstrated that S -allyl-L-cysteine, a water-soluble component of Allium species [21, 22], promotes cell proliferation and neuroblast differentiation in the dentate gyrus [7]. In addition, we have shown the neuroprotective effects of Z -ajoene, an oil-soluble component, against ischemic damage in the gerbil hippocampus [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that fresh garlic extracts, garlic oil, garlic-derived chemicals and specific organo sulfur compounds generated by processing garlic could have neuroprotective effects via its anti-neuroinflammatory and anti-oxdative properties [23, 25, 48]. Allicin, isolated from galin oil, showed the strongest inhibition of acetylcholinesterase and butyrylcholinesterase enzymes [49].…”
Section: Discussionmentioning
confidence: 99%